Effect of different activator combinations on the properties of fly ash based geopolymer - Nematollahi, B.; Sanjayan, J.; Shaikh, Faiz (ACF., 2014)
This paper presents the effects of four different activator combinations including twosodium-based (Na-based) and one potassium-based (K-based) activator combinationsin the form of solution and one calcium-based (Ca-based) activator combination in theform of powder on the properties of fresh and hardened low calcium (Class F) fly ashbased geopolymer. The first Na-based activator combination (Na-based-1) is composedof 8.0 M NaOH solution (28.6% w/w) and Nea2SiO3 solution (71.4% w/w) with aSiO2/Na2O ratio of 2.0; whereas, the second Na-based activator combination (Nabased-2) is composed of only 8.0 M NaOH solution. The K-based activator combinationis composed of 8.0 M KOH solution (28.6% w/w) and K2SiO3 solution (71.4% w/w)with a SiO2/K2O ratio of 2.23. The Ca-based activator combination is in powder formcomposed of Ca(OH)2 (88.3% w/w) and Na2SiO3 (11.7% w/w) with a SiO2/Na2O ratioof 2.0. A counterpart ordinary Portland cement (OPC) mix with water to cement ratiocorresponding to the activator solution to fly ash ratio of the geopolymer mixturehaving the highest compressive strength was also made for comparison. Properties ofthe mixtures including workability of the fresh paste, density and compressivestrength were evaluated. Experimental results revealed that the geopolymer mix madeby the Ca-based activator exhibited the highest workability but the lowest compressivestrength. The geopolymer mix made by the Na-based-1 activator demonstrated thehighest compressive strength among all geopolymer mixtures. Furthermore, itexhibited superior workability and compressive strength with lower density comparedwith those of the counterpart OPC mix.